An Overview on Transdermal Drug Delivery System - Maurya, Vijay Bahadur; Kumar, Vinay; Kumar, Rajeev (Journal of Drug Delivery and Therapeutics, 2019)
Transdermal drug delivery is involved in the transportation of drug through the skin for systemic circulation. Now a day’s more than 74% of drugs are administered drug in the form of tablet, capsule, which are taken orally but sometimes those are not effective as desired due to physiological activities of body. The major obstruction caused by stratum corneum to penetrate the drug. So there is need to facilitate the stratum corneum to increase the flux, a number of approaches are used to enhance the penetration of drug. Transdermal drug delivery system (TDDS) are very effectively overcome the hepatic first pass metabolism and improve the steady plasma drug concentration. The present review article provides an overview of various types of transedrmal patches, method of preparation and their evaluation.Keywords- Transdermal drug delivery system, First pass metabolism, TDDS